2008
DOI: 10.1111/j.1365-2133.2008.08881.x
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for the diagnosis and management of vitiligo

Abstract: Summary This detailed and user‐friendly guideline for the diagnosis and management of vitiligo in children and adults aims to give high quality clinical advice, based on the best available evidence and expert consensus, taking into account patient choice and clinical expertise. The guideline was devised by a structured process and is intended for use by dermatologists and as a resource for interested parties including patients. Recommendations and levels of evidence have been graded according to the method dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
288
1
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(317 citation statements)
references
References 122 publications
5
288
1
14
Order By: Relevance
“…4,8 In this context, NB-UVB phototherapy is recommended in preference to oral PUVA because of evidence of greater efficacy and safety, as well as because of the substantial repigmentation rates that are achieved, particularly on the face, trunk and proximal extremities. 1,4,[24][25][26] In this regard, a lower likelihood of erythema and xerosis development, carcinogenic effects and a lack of oral treatment obligation were reported advantages of NB-UVB phototherapy when compared with PUVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8 In this context, NB-UVB phototherapy is recommended in preference to oral PUVA because of evidence of greater efficacy and safety, as well as because of the substantial repigmentation rates that are achieved, particularly on the face, trunk and proximal extremities. 1,4,[24][25][26] In this regard, a lower likelihood of erythema and xerosis development, carcinogenic effects and a lack of oral treatment obligation were reported advantages of NB-UVB phototherapy when compared with PUVA.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 This indicated that a wavelength of around 311 nm had a favourable safety profile and was clinically more effective than full-spectrum UVB. Since then, NB-UVB phototherapy has been used as a first-choice strategy for most vitiligo patients, 8 as an alternative to the mainstay of treatment for generalized and focal vitiligo, which utilizes psoralen plus UVA (PUVA) photochemotherapy and topical corticosteroids (such an approach has been used for many years). 9 Narrowband-UVB has been reported to be a good wavelength to which vitiligo responds.…”
Section: Introductionmentioning
confidence: 99%
“…В последние годы одним из патогенетических методов лечения считают применение местных ан-тиоксидантов и УФ-В-терапию (UVB TL01) с дли-ной волны 311 нм [4,7,8]. Разработан гель Вити-скин, который содержит супероксиддисмутазу, спо-собствующую нейтрализации свободных радикалов, благодаря чему стимулируется общий метаболизм в клетках [4,7].…”
Section: Abstract: Vitiligo Vitiskin Gel Uvb 311 Nmunclassified
“…Разработан гель Вити-скин, который содержит супероксиддисмутазу, спо-собствующую нейтрализации свободных радикалов, благодаря чему стимулируется общий метаболизм в клетках [4,7]. Витискин относится к гидрогелям, действующим на всех уровнях регулирования депиг-ментации.…”
Section: Abstract: Vitiligo Vitiskin Gel Uvb 311 Nmunclassified
“…actualmente, disponemos de diversas aproximaciones terapéuticas para esta patología, las que dependen principalmente de la extensión del compromiso cutáneo y del tipo de piel, sin embargo, no existe hasta el momento un tratamiento completamente efectivo 3 .…”
unclassified